Length-weight relationshisp and relative conditions factor for the halfbeak Hemiramphus far ForsskÃ¥l , 1775 from the Karachi coast (University Journal of Zoology, Rajshahi University, 2009)
No Abstract Key words: Hemiramphus far, Karachi fish Harbour,Karachi coast,length-weight relationship, condition factor, allometric growth. doi:10.3329/ujzru.v27i0.1967 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 103-104